2016
DOI: 10.15376/biores.11.4.johnson
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Biorefinery into an Operating Kraft Mill

Abstract: Kraft pulp and paper mills have several advantages for serving the emerging biorefinery industry as a source of raw materials. This review examines technologies for producing liquid biofuels, chemicals, and advanced materials from woody feedstocks to generate new sources of revenue. Market pull comes in part from government policies that drive substitution of petroleum-based products with biobased equivalents. Kraft mills have ample networks to supply feedstocks, whether these are forest residues or byproduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 124 publications
1
13
0
Order By: Relevance
“…Such processing is consistent with the concept of a biorefinery (Kamm and Kamm 2004;Fernando et al 2006;Amidon et al 2008). Various forms of biorefineries have existed for decades with the most notable being the kraft pulp and paper mill (Yoon and van Heiningen 2008;Kautto et al 2010;Jun et al 2012;Johnson and Hart 2016). The…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Such processing is consistent with the concept of a biorefinery (Kamm and Kamm 2004;Fernando et al 2006;Amidon et al 2008). Various forms of biorefineries have existed for decades with the most notable being the kraft pulp and paper mill (Yoon and van Heiningen 2008;Kautto et al 2010;Jun et al 2012;Johnson and Hart 2016). The…”
Section: Introductionsupporting
confidence: 75%
“…Mixed results were also reported for the impact of various VPP treatments on tear strength. Several researchers reported an increase in tear index between 30% and 50% for handsheets after VPP (Yoon et al 2008;Kautto et al 2010;Jun et al 2012;Liu et al 2012). Helmerius et al (2010) observed essentially no change in other strength properties but also reported a similar increase in tear strength after HWE prior to kraft pulping silver birch (Betula pendula).…”
Section: Machine Made Paper Properties Comparative Datamentioning
confidence: 97%
See 2 more Smart Citations
“…After washing, a last filtration and drying step is included. The precipitation and washing procedure is comparable to the LignoBoost® process and enables the usage of similar equipment and already present know-how (Johnson and Hart, 2016;Tomani, 2010). The permeate of the washing solution and low pH H 2 O is fed to the recovery cycle of the pulp mill and contains 324 kg/h of H 2 O solubles originating from the lignin.…”
Section: Techno-economic Analysismentioning
confidence: 99%